Synergy of nuclear data systematics and proxy-SU(3) in planning future experiments in the superheavies mass region - Peroulis, S. P.; Bofos, S.; Mertzimekis, T. J.; Martinou, A.; Bonatsos, D. (HNPS Advances in Nuclear Physics, 2019)
Spectroscopic information of hard–to–reach superheavy nuclei can be invaluable in understanding the dynamics of nuclear systems at large values of charge and volume. RIB factories of the next generation, such as FAIR, plan to provide heavy ion beams at high energies to facilitate experimental access to these mass regimes. In preparation of future experimental endeavours, a systematic survey of available nuclear data, mainly energies and reduced transition probabilities/lifetimes of short–lived 21+ states in even–even isotopes with Z=82,84,86 was undertaken. The principle motivation is to trace the competition between collective and single-particle degrees of freedom in the mass area just above Pb (Z=82), an area known to exhibit isomerism, octupole degrees of freedom and shape coexistence. Existing data were compared to the theoretical predictions using the analytical, parameter–free proxy–SU(3) scheme, for neutron numbers N=96–116. The model was further employed to predict currently unknown values for spectroscopic data in series of Pb, Po and Ra isotopes.